(untitled) (Pharmacology & Toxicology Research (ISSN 2349-4581), 2024)
Autism Spectrum Disorders (ASD) are neurodevelopmental disorders characterized by varying deficits in social interactions, communication, and learning, as well as stereotypic behaviors. Despite the significant increasing rates of ASD during the last two decades, there are few clues for its exact pathogenesis, delaying early detection and effective intervention. Thus, identifying causes and treatments is imperative. So far, there are no known efficacious treatments for the core social symptoms, although effects on repetitive behaviors are indicated with some data. During the past decade oxytocin (OT) research has shown a major upsurge. The beneficial roles of OT on social functioning raise the question regarding its potential usefulness in ASD management. If clinical application of OT in the treatment of ASD proves successful then it may introduce a new hope for afflicted individuals and their families. Fortunately pioneering clinical studies support this notion; however, more research should go on to resolve issues concerning clear mechanisms by which OT modulates social behavior before its real introduction for clinical application. Also probable adverse affects must be thoroughly investigated to ensure safe treatment outcomes